Putting the public at the heart of the NHS. Issue 7584 (11th January 2007) - Hutton, Will
Abstract : With the public's demand for improved service provision and accountability of service providers, Will Hutton explains why the NHS needs to embrace deliberative democracy better to respond to public expectations